2009
DOI: 10.1016/j.jaerosci.2009.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Error source in AOD retrieval from filter radiometer data in the UV due to filter band function

Abstract: The filter band function of filter radiometers is frequently used in AOD retrieval to improve the accuracy of the Rayleigh and gaseous absorption contributions to the total optical depth. These contributions to the total optical thickness are overestimated when the band-pass filter curve used in the computation exceeds the lower limit of the detector response range (around 320 nm). It can be the case for some typical band-pass filters used in the ultraviolet region (e.g. 340 or 380 nm). This error can involve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…However, the importance of using different narrowband filter responses was not clearly established in this study. Ortiz de Galisteo et al (2009) showed the importance of the "wings of the filter" effect, which might introduce an overestimation in the aerosol optical depth, and thus inaccuracies in PWV retrieval due to uncertainties on Rayleigh and gaseous absorption total optical depth. This problem was also studied by Alexandrov et al (2009).…”
Section: The New Lunar Cimel Ce-318umentioning
confidence: 99%
“…However, the importance of using different narrowband filter responses was not clearly established in this study. Ortiz de Galisteo et al (2009) showed the importance of the "wings of the filter" effect, which might introduce an overestimation in the aerosol optical depth, and thus inaccuracies in PWV retrieval due to uncertainties on Rayleigh and gaseous absorption total optical depth. This problem was also studied by Alexandrov et al (2009).…”
Section: The New Lunar Cimel Ce-318umentioning
confidence: 99%
“…However, the importance of using different narrowband filter responses was not clearly established in this study. Ortiz de Galisteo et al (2009) showed the importance of the "wings of the filter" effect, which might introduce an overestimation in the aerosol optical depth, and thus inaccuracies in PWV retrieval due to uncertainties in Rayleigh and gaseous absorption total optical depth. This problem was also studied by Alexandrov et al (2009).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, UV wavelengths are especially difficult to calibrate for several reasons, either with the Langley plot method or by comparison (Slusser et al, 2000). In summary, special care must be taken when analysing AOD at UV wavelengths (Ortiz de Galisteo et al, 2009).…”
Section: Aerosol Input Parametersmentioning
confidence: 99%